KETERKAITAN KARAKTERISTIK DAN PENDAPATAN PETANI UBI JALAR - Elly Elly Rasmikayati1; Tuti Karyani; Bobby Rachmat Saefudin (Agros Journal of Agriculture Science, 2023)
Sweet potato farmers in Arjasari sub-district already have enough experience in farming, their income should tend to increase. However, in reality the income of sweet potato farmers in Arjasari District still fluctuates. This study aims to describe the characteristics of farmers, sweet potato production, and sweet potato farming income. This study also identified the feasibility of farming, farming characteristics, farm income and analyzed the relationship between the characteristics and income of sweet potato farming in Arjasari District. This research using secondary data from sweet potato farmers in Arjasari District with a sample of 110 people. Data were processed using descriptive statistical analysis, R/C ratio, and Chi-square test. The results showed that the individual characteristics of sweet potato farmers in Arjasari District included an average age of 41 to 60 years old farmers, with the last education at the elementary school level. Analysis of the feasibility calculation of sweet potato farming is proven by the R/C value which is 1.1. There is also a relationship between farmer education and sweet potato farmer farm income. INTISARIPetani ubi jalar di kecamatan Arjasari sudah memiliki cukup pengalaman dalam berusaha tani, seharusnya pendapatan yang diperoleh cenderung semakin meningkat. Akan tetapi, kenyataannya penghasilan petani ubi jalar di Kecamatan Arjasari masih berfluktuasi. Penelitian ini bertujuan untuk mendeskripsikan karakteristik petani, hasil usahataninya, kelayakan usahanya dan hubungan antara antara karakteristik petani dengan pendapatannya. Penelitian ini dilakukan dengan menggunakan data sekunder dari petani ubi jalar di Kecamatan Arjasari dengan sampel sebanyak 110 orang. Data diolah dengan menggunakan analisis statistika deskriptif, R/C ratio, dan uji Chi-square. Hasil penelitian menunjukkan karakteristik individu petani ubi jalar di Kecamatan Arjasari meliputi rata-rata petani berusia 41 hingga 60 tahun, dengan berpendidikan terakhir setingkat dengan sekolah dasar. Analisis perhitungan kelayakan usahatani ubi jalar dibuktikan dengan nilai R/C yang bernilai 1,1. Terdapat juga keterkaitan antara pendidikan petani dengan pendapatan usahatani petani ubi jalar.